2022
DOI: 10.1007/s10965-022-03104-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and assessment of poly(5-nitro-2-aminophenol) as a new scaling inhibitor to control the precipitation of CaCO3 and CaSO4 in solution

Abstract: The introduction of a -NO2 substituent in o-aminophenol would create an open-unit polymer suitable for different applications. We report the synthesis of poly(5-nitro-2-aminophenol) by aniline-catalyzed oxidative polymerization. The polymer structure was intensively characterized by spectroscopic techniques, elemental analysis, cyclic voltammetry, electrical conductivity and microscopic measurements such as SEM, TEM, TGA and DSC. The hydrophilic and hydrophobic nature of the substituents provided the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Adsorption kinetics and isotherms studies Different kinetic models are used to analyze the experimental data of different concentrations of safranin dye (20,30,40, 50 ppm for 75 min, 25 °C, 2 g / L adsorbent dose) for copolymer 6 and nanocomposite 7 according to equations of pseudo first order and pseudo second order, discussed later in the results section. Also, Langmiur and Freuindish isotherm types were investigated for different concentrations of safranin dye for copolymer 6 and nanocomposite 7 according to its equations, discussed later in the results section.…”
Section: Effect Of Various Concentration Of Safranin Dye Verses Conta...mentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorption kinetics and isotherms studies Different kinetic models are used to analyze the experimental data of different concentrations of safranin dye (20,30,40, 50 ppm for 75 min, 25 °C, 2 g / L adsorbent dose) for copolymer 6 and nanocomposite 7 according to equations of pseudo first order and pseudo second order, discussed later in the results section. Also, Langmiur and Freuindish isotherm types were investigated for different concentrations of safranin dye for copolymer 6 and nanocomposite 7 according to its equations, discussed later in the results section.…”
Section: Effect Of Various Concentration Of Safranin Dye Verses Conta...mentioning
confidence: 99%
“…As a part of an ongoing project directed to new findings in the field of water treatment using functionalized polyanilines as highly promising candidates [18,19,20,21], we investigated the use of (aniline-co-aniline-2,5-disulfonic acid)/L-hexuronic acid/Ag@SiO 2 nanocomposites as a new highly anionic polyelectrolyte with an enhanced adsorptive effect for removing the cationic dye safranin. The incorporation of disulfonated units into the polymer chain should double the sulfonate groups on the backbone and produce regular molecular structure polymers with a higher sulfonation degree [22].…”
Section: Introductionmentioning
confidence: 99%
“…As part of an ongoing project directed to research in the field of using PANI and its functionalized analogues as multifunctional substrates for industrial application [21][22][23][24], we recently reported the chemical synthesis and characterization of poly(aniline-co-aniline-2,5disulfonic acid) and its composite containing L-hexuronic acid, Fig. 1, and metallic Ag/SiO2 nanoparticles, as an efficient, new, thermally stable anionic polyelectrolyte to remove safranin dye from aqueous media [25].…”
Section: Introductionmentioning
confidence: 99%